The Impact of Organizational Culture on Public Service Quality in the Baubau City Regional Secretariat - Marzuki; Herman Lawelai; Anwar Sadat; Nastia (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
This study aims to examine the effect of organizational culture on the quality of public services offered by the Baubau City Regional Secretariat. This study involves quantitative descriptive research, a technique used to assess the state of natural items in which the researcher is the principal instrument. The results of the SPSS test demonstrate that the sig value is known. The t value for the influence of organizational culture on the quality of public services is 4.418, which is more than 0.676. Consequently, the study's premise is accepted, indicating that organizational culture influences the quality of public services. According to the SPSS test, the R Square value is 0.394, indicating that organizational culture has a 39.4 percent influence on the quality of public services. The research findings indicate that 60.4% of variables beyond the scope of this study influence the quality of service at the Baubau City Regional Secretariat.